Relation of Neutrophil to Lymphocyte Ratio With the Presence and Severity of Stable Coronary Artery Disease. (July 2014) - Kaya, Ahmet; Kurt, Mustafa; Tanboga, Ibrahim Halil; Işık, Turgay; Günaydın, Zeki Yüksel; Kaya, Yasemin; Topçu, Selim; Sevimli, Serdar
Objectives: We examined the association between neutrophil to lymphocyte ratio (NLR) and the complexity of coronary artery disease assessed by SYNTAX score (SS). Methods: The study population included patients with chest pain who had undergone coronary angiography for stable angina pectoris. Patients were classified depending on whether the SS was 0 or SS > 0. Results: Left ventricular ejection fraction, estimated glomerular filtration rate, and NLR were found to be the independent predictors of high SS in multivariate analysis. The area under the receiver–operating curve of NLR was 0.72 (0.65-0.80, P < .001) for predicting high SS. The optimal cutoff value of NLR to predict high SS was 2.7 (sensitivity of 72% and a specificity of 61%). There was a significant correlation between NLR ratio and continuous SS ( r = .552, P < .001). Conclusion: The NLR is a readily measurable systemic inflammatory marker and is associated with both the presence and the complexity of coronary artery disease.